Pengaruh Jarak Tanam Terhadap Pertumbuhan Pohon dan Beberapa Sifat Fisis-Mekanis Kayu Jati Cepat Tumbuh - Imam Wahyudi; Dicky Kristia Dinata Sinaga; . Muhran; Lidia Binti Jasni (Institut Pertanian Bogor, 2014)
The aim of this study was to evaluate the effect of tree spacing or planting distance on tree growth characteristic and several physical and mechanical properties of fast growing teak (Tectona grandis) wood from a plantation area in West Java. Growth characteristics of all trees within the plot of each planting distance were evaluated, while physical-mechanical properties were represented by 6 selected trees of each planting distance. The results showed that growth characteristics were significantly influenced by tree spacing, while wood properties were not. The wider spacing (3 by 3 m) tends to produce bigger stem diameter, but shorter tree height, shorter clear bole height, and greater branches. Although tree spacing of 3 by 3 m is more favored by the farmers since it provides more space for agroforestry activity, such spacing is not recommended to be applied in order to produce the best timber from teak plantation.